The last ghetto : an everyday history of Theresienstadt - Hájková, Anna 1978- (Oxford University Press, 2020)
Introduction: The well-known, poorly understood ghetto -- 1. "The overorganized ghetto:" administering Terezin -- 2. A society based on inequality -- 3. The age of pearl barley: food and hunger -- 4. Medicine and illness -- 5. Cultural life: leisure time activities -- 6. Transports to the East